POTENTIAL FOR ROCK-POLISHING ENTERPRISES IN SOUTHWESTERN NIGERIA - Aigbedion I. (My University, 2007)
Various igneous and metamorphic rocks constitute the basement complex in much of southwestern Nigeria. They are composed of felsic to mafic constitutions, and textural characteristics are wide ranging. Based on petrographic and physical parameters, these rocks hold promise to be utilized for polished items. However, industrial exploitation may be constrained by a number of factors, in some cases by huge financial outlay, environmental pollution and insincerity from government agencies. A sustainable, viable project in ornament stones would demand further geological appraisals, technical facilities, adequate capital and relevant manpower. As in most developing countries, in Nigeria deposits of stones or high-grade geomaterials are commonly blasted indiscriminately, and especially in the southwest, thus there needs to be an awareness and concern for their conservation and environmental protection. Mining of rocks commonly results in environmental degradation; consequently, there is a need to design adequate monitoring and conservation strategies for effective exploitation.
Keywords: NIGERIA; STRENGTH INDEX; POINT LOAD STRENGTH; DIMENSION STONE; POINT LOAD STRENGTH INDEX